LITERASI MATEMATIKA SISWA DALAM MEMECAHKAN MASALAH HOTS - Siti Wulandari; Christina Kartika Sari; Adi Nurcahyo; Rini Setyaningsih (IKIP Siliwangi, 2023)
The purpose of this study was to analyze students' mathematical literacy abilities in solving High Order Thinking Skills (HOTS) questions on circle material. This study used descriptive qualitative method. The research subjects were 3 students of class VIII. Data collection in the study was carried out in two stages, the first stage was a written test. The second stage is an interview with 7 questions that have been adjusted to indicators of mathematical literacy. Checking the validity of the data using the triangulation technique compared the acquisition of interviews and tests. In conducting data analysis, it is divided into three components, namely data reduction, data presentation, and drawing conclusions. Based on the research results, all indicators of mathematical literacy have been achieved by students with high mathematical abilities. Meanwhile, students who have moderate mathematical abilities have achieved communication indicators, problem solving strategies, and representations. Finally, students who have low mathematical abilities have achieved indicators of problem solving and representation strategies.